Impact of Children's Social Behavior After Participating in The Program of Confident Children School - Soeprijono, Bambang; Bimantoro, Krisno; Saswini, Andi Ade Ula; Ramli, Muhammad; Alam, Syamsul; Nildawati, Nildawati (Diversity: Disease Preventive of Research Integrity, 2021)
One of the important aspects needed for early childhood is the aspect of self-confidence. Self-confidence is an attitude that will build him to interact in community life, the family environment and the school environment. This study is designed to evaluate the effectiveness of the Confidence Children's School as part of the CSR program of PT Pertamina Regional VII, South Sulawesi. This report presents an analysis of post-programme data collected from 30 children and 1 facilitator and 6 parents whose children attended the School for Confidence Children program. The data are then presented descriptively using the Likert scale and qualitatively to assess the effectiveness of this program. The results showed that 3 variables that support the Self-Confidence Children's School program, namely the content or material of the program, service during learning and the ability of the teaching staff to produce very good grades with criteria at the very satisfied level. In addition, the knowledge, actions and attitudes of students after participating in the school program are confident that each child has criteria for being at a good level. The Confident Children's School Program has immediate value for participating children and families as participants are equipped with skills to reduce emotional and behavioral difficulties.